Uric Acid, Colchicine and Chronic Inflammatory Diseases: A Cardiovascular Perspective - Alessia Alunno; Francesco Carubbi; Claudio Ferri (Metabolites)
Based on the notion that inflammation plays a pivotal role in the development and progression of cardiovascular diseases (CV) and that hyperuricaemia is an independent CV risk factor, chronic inflammatory diseases such as gout and rheumatoid arthritis are an interesting case study. Both conditions are burdened by an excess CV risk; they are themselves an independent CV risk factor, and in the case of gout, hyperuricaemia is a hallmark of the disease. Colchicine, a drug historically used for the management of gout, has recently been repurposed for secondary CV prevention in individuals at high CV risk. The purpose of this review article is to discuss evidence on CV diseases and CV prevention in rheumatoid arthritis, gout, and other chronic inflammatory/systemic autoimmune diseases with a focus on inflammation and hyperuricaemia.